A turn-on fluorogenic Zn(ii) chemoprobe based on a terpyridine derivative with aggregation-induced emission (AIE) effects through nanofiber aggregation into spherical aggregates. Issue 5 (1st October 2014) - Jung, Sung Ho; Kwon, Ki-Young; Jung, Jong Hwa
Abstract : The self-assembly of the terpyridine-based ligand exhibited strong emission in the presence of Zn 2+ due to the formation of coordination bonds between the terpyridine moieties and the Zn 2+ by the aggregation-induced emission effect. Abstract : The self-assembly of a terpyridine-based ligand in a DMSO/water solvent mixture (1 : 99 v/v) with a high content of water formed a nanofibrillar structure and showed a non-emissive process. On the other hand, the self-assembly of the terpyridine-based ligand exhibited strong emission in the presence of Zn 2+ due to the formation of coordination bonds between the terpyridine moieties and the Zn 2+ by the aggregation-induced emission effect. The morphology of this aggregate represented a spherical structure.